Winters, Ed., The Civil Rights Movement; Siebold, Ed., Martin Luther King, Jr. - Swedberg, Sarah (Teaching History: A Journal of Methods, 2002)
These two anthologies from Greenhaven Press focus on the modern civil rights movement. The Civil Rights Movement focuses on the period from 1954 to the present, and Martin Luther King, Jr. on the impact of Martin Luther King, Jr. on that movement. Both anthologies work to provide some useful information on civil rights for a high school or introductory-level college audience.